Energy absorption and mechanical performance of kenaf yarn/fibreglass mesh/acrylonitrile butadiene styrene composites: Influence of mesh density - Mohamad Yusuf Salim; Muhamad Fauzi Muhammad Fitri; Muhammad Asyraf Muhammad Rizal; Rushdan Ahmad Ilyas; Mohd Haziq Dzulkifli; Shukur Abu Hassan; Abu Bakar Mohd Supian; Muhammad Rizal Razman (Journal of Materials Research and Technology)
Kenaf-based composites have environmental and economic benefits, but their mechanical performance is generally inferior to synthetic composites, restricting their use in load-bearing automobile components. A solution is to hybridise kenaf fibres with synthetic reinforcements like fibreglass mesh. The best fibreglass mesh structure and density for mechanical performance and lightweight properties are unknown. This study examines how fibreglass mesh densities affect kenaf yarn-based hybrid composite energy absorption and mechanical performance and identifies combinations for demanding automotive applications that align with the 12th Sustainable Development Goal. Moreover, the study explores the synergistic effects of mesh density on the composite's mechanical performance. The composites were fabricated using a hot compression-moulding process, stacking the kenaf fibres in 0°/45°/-45°/90° orientations, with acrylonitrile butadiene styrene (ABS) as the matrix. The stacking sequence for the kenaf/fibreglass mesh/ABS composites followed a GKKGKKG pattern. Three different fibreglass mesh densities were tested: 1 mm2 (KGFM-1/fine), 3 mm2 (KGFM-3/medium), and 5 mm2 (KGFM-5/coarse), with results compared to kenaf/ABS composites (control sample). The experimental results showed that the KGRP-5 composite, featuring the 5 mm mesh, demonstrated superior resistance to indentation, withstanding a load of 3403.8 N. It absorbed 41.8 J of energy, with a specific energy absorption of 482.1 J/kg. Additionally, KGRP-5 exhibited excellent flexural performance, achieving a flexural strength of 76.1 MPa and a stiffness of 1323 MPa. Furthermore, the KGRP-5 composite achieved the highest short-beam shear strength of 9.6 MPa. This makes the hybridised composite with coarse mesh density a promising candidate for automotive components.